Issues in the management of public service institutions - Ejiogu, Aloy M. (Aloy Maduka) (Ikeja, Nigeria : Pumark Nigeria, 1994)
Examines the nature and problems of the Nigerian Public/Civil Service and then offers a few hints on how such bodies can be managed effectively and efficiently whether or not they are privatized/commercialized.
Includes bibliographical references.
oif 13/03/15
Loan
Keywords: Administrative agencies -- Nigeria -- Management; Executive departments -- Nigeria -- Management; Public institutions -- Nigeria -- Management; Civil service -- Nigeria